Diabetes and Risk of Cancer. (7th February 2013) - Habib, Samy L.; Rojna, Maciej
Abstract : Diabetes and cancer represent two complex, diverse, chronic, and potentially fatal diseases. Cancer is the second leading cause of death, while diabetes is the seventh leading cause of death with the latter still likely underreported. There is a growing body of evidence published in recent years that suggest substantial increase in cancer incidence in diabetic patients. The worldwide prevalence of diabetes was estimated to rise from 171 million in 2000 to 366 million in 2030. About 26.9% of all people over 65 have diabetes and 60% have cancer. Overall, 8–18% of cancer patients have diabetes. In the context of epidemiology, the burden of both diseases, small association between diabetes and cancer will be clinically relevant and should translate into significant consequences for future health care solutions. This paper summarizes most of the epidemiological association studies between diabetes and cancer including studies relating to the general all-site increase of malignancies in diabetes and elevated organ-specific cancer rate in diabetes as comorbidity. Additionally, we have discussed the possible pathophysiological mechanisms that likely may be involved in promoting carcinogenesis in diabetes and the potential of different antidiabetic therapies to influence cancer incidence.